Periarticular Injection with Bupivacaine for Postoperative Pain Control in Total Knee Replacement: A Prospective Randomized Double-Blind Controlled Trial - Varah Yuenyongviwat; Chaturong Pornrattanamaneewong; Thitima Chinachoti; Keerati Chareancholvanich (Advances in Orthopedics)
Background. Local periarticular injection with bupivacaine alone in TKA has not been studied. Thus, we aimed to examine the effectiveness of local periarticular injection with bupivacaine for post-operative pain control in TKA. Method. Sixty patients undergoing TKA by a single surgeon were randomly assigned into two groups in a double-blind, placebo-controlled study. In the injection group, patients received periarticular injections with 0.25% bupivacaine before wound closure; in the control group, patients received a 0.9% normal saline injection. Both groups received the same anesthetic procedure, post-operative pain control, and rehabilitation protocol. Results. There was a significant reduction in post-operative morphine consumption in the first six hours after the operation (mean 0.9 mg and 2.43 mg, P=0.01), but there was no significant difference in post-operative morphine consumption between six hours and ninety-six hours after the operation, visual analogue scale (VAS) score, morphine side effects during the first 96 hours, length of hospital stay, or complications from morphine consumption. Conclusion. Local periarticular injection with bupivacaine alone before wound closer was shown to be an effective method to improve pain control after TKA with a few complications and ease of use.